Challenges to change laboratory learning in a dynamic and complex civil construction project - Lopes, Manoela Gomes Reis; de Gouveia Vilela, Rodolfo Andrade; Querol, Marco Antonio Pereira; de Almeida, Ildeberto Muniz [UNESP] (Springer Nature, 2019)
The chapter presents a Change Laboratory (CL) intervention in the construction airport activity. After the occurrence of two severe accidents in a brief time interval, the Labor Prosecution Office sought the School of Public Health to assist at the second accident analysis. The application of Analysis and Prevention of Accidents' Model (MAPA) and CL appeared as a proposal. During the implementation process, the activity was in a crisis phase. The participants identified the problems, but they felt paralyzed in some moments. The CL allowed the participants to formulate hypotheses of the main problems and their relation with historical changes in the activity. The CL allowed the creation of solutions, but with the shutdown of the construction site, it was not possible to have continuity in the implementation of solutions. In the chapter will be presented the results achieved, the difficulties faced, and proposition of suggestions for actions to improve and continue the development of the activity.